On the Extent of Tyrosine Phosphorylation in Chloroplasts - Lu, Qintao (Plant Physiol, 2015)
Reanalysis of published mass spectrometry data on Tyr-phosphorylated chloroplast proteins indicates that the majority of peptide spectrum matches reporting Tyr phosphorylation are ambiguous.